BUSCA ATIVA NA UNIDADE BÁSICA DE SAÚDE DE PACIENTES COM TUBERCULOSE: UM ESTUDO DE CASO - Alfing, Cleide E. d. S.; Cardoso, Elenara R.; Loro, Marli M.; Bonfada, Sonia T. (Salão do Conhecimento, 2013)
Resumo